Basic Accounting Concepts. (Book). - Buzby, Stephen L.; Spiller, Earl A. (The Accounting Review, 1975)
Abstract Reviews the book "Basic Accounting Concepts," by Hershel M. Anderson, James W. Giese and Bernard A. Coda.